Implementasi Markerless Augmented Reality untuk Mendukung Penjualan Furnitur - Wiwin Susanty; Erlangga Erlangga; Taqwan Thamrin; Rexy Hari Rafsanjani; Usman Rizal (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
Technological developments in recent years have experienced very rapid changes, especially in the field of promotion and visuals. With the development of techniques that affect these aspects, it brings many changes that make it easier for the community, and at certain stages become problem solvers. In this study, a markerless Augmented Reality (AR) application that supports furniture sales will be designed. This application allows users to see the desired furniture product in 3D without using a marker that can be run in real-time. So far, to see pictures of furniture products, consumers have to come directly to the store to see the products they need. Alternatively, consumers can view the catalogs available on social media at the store or stores they visit. This study uses the AR method without markers. This eliminates the need for users to use one or more markers as recognition targets to display visual objects in furniture products. Unlike other applications, this application can be used as a medium to support sales of furniture that is more attractive because it can provide detailed information about all furniture products that are visualized interactively in 3D so that it can support furniture sales promotions.